PENGARUH PENGGUNAAN INSTAGRAM DAN WHATSAPP TERHADAP KREATIVITAS BERMARTURIA MAHASISWA PRODI TEOLOGI IAKN TARUTUNG TAHUN 2019 - Devi Afriani Barus (IAKN Tarutung, 2020)
AbstractThe research hypothesis is related to the positive and significant use of Instagram and WhatsApp on the creativity of students of Tarutung's IAKN Theology study program in 2019.The research used a descriptive quantitative inferential techniques, with population its all 2019/2020 Academic Year Theology Study Program students departing 206 people. Sampling using Random Sampling technique by 20% of the population of 41 people.The results of the analysis of rxy = 0.537 rtable = 0.308 and tcount = 3.973 ttable = 2.021 show that there is a relationship between Instagram and WhatsApp use with the creativity of students with Tarurung IAKN Theology Theology study program in 2019 and obtain the significance of a simple regression equation. Hypothesis testing obtained Fcount = 15.682 Ftable = 1.51 then H0 is rejected and Ha is accepted.Keywords: Using Instagram and WhatsApp, marturia creativity